ANSWER
[tex]y = - 4 {x}^{2} + 4x - 3[/tex]
EXPLANATION
Let the quadratic function be
[tex]y = a {x}^{2} + bx + c[/tex]
We substitute each point to find the constants, a,b, and c.
Substitute: (x=0,y=-3)
[tex] - 3 = a {(0)}^{2} + b(0) + c[/tex]
[tex] \implies \: c = - 3...(1)[/tex]
Substitute: (x=-1,y=-11) and c=-3
[tex] - 11 = a {( - 1)}^{2} + b( - 1) + - 3[/tex]
[tex] \implies \: - 11 = a - b - 3[/tex]
[tex] \implies \: a - b = - 8...(2)[/tex]
Substitute: (x=3,y=-27) and c=-3
[tex] -27= a {( 3)}^{2} + b( 3) + - 3[/tex]
[tex] \implies \: - 27 = 9a + 3b - 3[/tex]
[tex]\implies \: 3a + b = - 8...(3)[/tex]
Add equations (3) and (2)
[tex]3a + a = - 8 + - 8[/tex]
[tex]4a = - 16[/tex]
[tex]a = - 4[/tex]
Put a=-4 in equation (2)
[tex] - 4 - b = - 8[/tex]
[tex] - b = - 8 + 4 [/tex]
[tex] - b = - 4[/tex]
[tex]b = 4[/tex]
The quadratic equation is
[tex]y = - 4 {x}^{2} + 4x - 3[/tex]